Studi Kritis Terhadap Praktik E-Begging Dalam Tiktok Live Menurut Pemahaman Hadis Dan Prinsip Etika Sosial - Pratama, Dicky Wahyu; Hasanah, Uswatun; Nadhiran, Hedhri (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
Abstract The phenomenon of E-Begging in TikTok live streaming is increasingly becoming a concern in today's digital era. E-Begging, which is the practice of asking for help online, utilizes the live streaming feature to attract viewers and obtain virtual gifts as a form of support. This study aims to analyze this phenomenon from the perspective of the hadith, especially those related to ethics and morals in a social context (interpersonal relationships). In this study, a qualitative approach with thematic-conceptual methods was used to explore the meaning and awareness of the practice of E-Begging. The results of the study show that begging without an emergency is an act that is prohibited in Islam. The Prophet Muhammad ﷺ emphasized the importance of trying and seeking sustenance in a halal way. Therefore, the phenomenon of E-Begging not only reflects social problems such as poverty and economic instability, but also raises ethical questions regarding human dignity and values ​​in society. Through this study, it is hoped that the public can better understand the negative impacts of E-Begging and encourage discussions about more constructive solutions to help those in need without degrading their dignity. This study also recommends the need for collective awareness not to support practices that are detrimental both socially and morally.